IUS CONSTITUENDUM PERTANGGUNGJAWABAN PIDANA PENGGUNA JASA PROSTITUSI ONLINE - Ade Rizkia Arumdani Rusdi; Fenty Puluhulawa; Dian Ekawaty Ismail (Universitas Muara Bungo, 2023)
The purpose of this study was to identify and analyze criminal liability for users of online prostitution services from the aspects of Indonesian criminal policy and the ius constituendum for criminal liability for users of online prostitution services in Indonesia. The type of research used is Normative Law research, using a statute approach and a conceptual approach. Furthermore, it is arranged systematically to obtain a complete picture, and the researcher processes it using analytical descriptive techniques. The results of this study indicate that the criminal responsibility of users of online prostitution services in Indonesia can be seen in the regulations contained in the scale of laws and regional regulations. Meanwhile, in several of these laws there is still a legal void for users of prostitution services to be subject to criminal liability. Furthermore, the criminal responsibility of users of online prostitution services in the upcoming criminal policy (ius constituendum) is expected to be able to answer the problem of online prostitution crimes. As far as its development goes, the regulations that apply are no longer in accordance with the needs of the community or what the community aspires to have a deterrent effect on users of prostitution services. Thus, there is no longer any form of legalized sexual intercourse that can harm society in material and moral forms.